Loyalitas Pekerja Sosial Yayasan Solidaritas Perempuan untuk Kemanusiaan dan Hak Asasi Manusia (SPEK-HAM) Surakarta - Rahayu Purwaningsih; Sudarwati; Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research is to examine and analyze the influence of welfare assurance, organizational culture, incentives, and rewards on the loyalty of social workers at the Women's Solidarity Foundation for Humanity and Human Rights (SPEK-HAM) Surakarta. A quantitative descriptive approach was employed to collect and analyze data through survey methods and regression analysis techniques. The population and sample in this study comprised all social workers at the Women's Solidarity Foundation for Humanity and Human Rights (SPEK-HAM) Surakarta, totaling 35 people. As the entire population in this study was utilized as a sample, this study employed non-probability sampling with saturation technique. Data collection techniques employed observation, documentation, and questionnaire methods, while the data analysis technique in this study used multiple linear regression analysis. This research confirms that welfare assurance, organizational culture, incentives, and rewards have a significant influence on the loyalty of social workers at SPEK-HAM Foundation Surakarta. The variables under investigation contributed 72.4% to the loyalty of social workers, while the remaining 27.6% was influenced by other variables not examined in this study. Effective management of welfare assurance, organizational culture, incentives, and rewards is imperative to enhance the loyalty of social workers and ensure the sustainability of the organization in achieving its vision and mission. Keywords: Loyalty, Welfare Security, Organizational Culture, Incentives, Rewards